Interobserver Agreement of the Static Methods of Evaluating the Types of Footprint in Runners - Rafael Rocha Macedo; Thiago Kazunori Neves Kanashiro; Gustavo Henrique Ramalho de Mattos; Alexandre Alcaide; Luciano Miller Reis Rodrigues; Eiffel Tsuyoshi Dobashi (Revista Brasileira de Ortopedia)
Abstract Objective To evaluate the accuracy of interobserver diagnostic methods of the type of footprint among running athletes using three evaluation methods: physical examination, podoscopy, and baropodometry compared with radiographic measurement of Meary angles and calcaneal pitch. Methods This is a cross-sectional study of athletes who practice running. The inclusion criteria were: individuals with minimum age of 18 years and maximum age of 65, male or female, healthy and without comorbidities that interfere with running performance; regular practitioners who run at least twice a week; body mass index between 18.5 and 29.99 Kg/m2; acceptance of the written informed consent form (WICF). The non-inclusion criteria included: presence of previous or active injuries that compromise sports activity; previous foot surgeries; obesity. Forty patients were selected, 29 (72.5%) male and 11 (27.5%) female, whose mean age was 39 years (minimum 19 years and maximum 61 years). The body mass index (BMI) of the 40 patients ranged from 21.00 to 29.99 kg/m2 (mean 25.48 kg/m2 with standard deviation of 2.39 kg/m2 and a median of 25.50 kg/m2). We excluded those with values above 29.99. Running frequency ranged from 2 to 5 times per week (average 3.13 times per week, with standard deviation of 0.79 times per week and median of 3 times per week). Physical examination, podoscopy, and baropodometry were performed, and their evaluation was made by 4 examiners. Additionally, the results were compared with the radiographic classification of the footprint type obtained by measuring the Meary angles and the calcaneal pitch. Results The interobserver agreement of these parameters was verified by the weighted Kappa agreement index, in which we obtained a significant agreement between the participants considering physical examination, podoscopy, and baropodometry, and according to the Kappa index. The agreement was marginal when comparing the results of the three methods with the radiographic angular classification. Conclusion We obtained excellent agreement among observers when considering physical examination, podoscopy, and baropodometry for the diagnosis of the footprint type among runners. However, when comparing the results obtained with the radiographic measurements, the agreement for the diagnosis of footprint type was low.